9x-5y=-25 and 5y-9x=25

That is twice the same problem so no solution possible as it is one problem with 2 variable

Posted on Jul 01, 2008

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

solution is:

x-5y = 20

-5y = 20-x

5y = x-20

y = (x-20) / 5

x-5y = 20

-5y = 20-x

5y = x-20

y = (x-20) / 5

Dec 14, 2015 | Office Equipment & Supplies

1) 2x + 5y = 7

2) 3x + 6y = 3

I'm going to use the method of elimination to solve for x and y.

Multiply 1) by 3 and 2) by 2 to allow the x's to be eliminated.

1) 6x + 15y = 21

2) 6x + 12y = 6

Now subtract line 2 from line 1.

0x + 3y = 15

---- ----

3 3 divide both sides by 3 to get y by itself.

y =5.

Substitute into 1) to calculate x.

2x + 5(5) = 7

2x + 25 = 7

2x + 25 -25 = 7 - 25

2x = -18

---- ----- divide both sides by 2 to get x by itself

2 2

x = -9

Check by plugging in answer into the other equation, in this case 2)

3 (-9) + 6(5) = 3

-27 + 30 = 3

3 = 3

We did it correctly and checked to prove that we did it right.

Good luck.

Paul

2) 3x + 6y = 3

I'm going to use the method of elimination to solve for x and y.

Multiply 1) by 3 and 2) by 2 to allow the x's to be eliminated.

1) 6x + 15y = 21

2) 6x + 12y = 6

Now subtract line 2 from line 1.

0x + 3y = 15

---- ----

3 3 divide both sides by 3 to get y by itself.

y =5.

Substitute into 1) to calculate x.

2x + 5(5) = 7

2x + 25 = 7

2x + 25 -25 = 7 - 25

2x = -18

---- ----- divide both sides by 2 to get x by itself

2 2

x = -9

Check by plugging in answer into the other equation, in this case 2)

3 (-9) + 6(5) = 3

-27 + 30 = 3

3 = 3

We did it correctly and checked to prove that we did it right.

Good luck.

Paul

Mar 12, 2015 | Office Equipment & Supplies

This is best written as two separate equations:

8x+3y = -23 and 34x+ 5y = -23

Solving the first one for x:

8x = -23-3y

x = -23/8 - 3/8y

Substituting this value for x into the second equation:

34(-23/8 - 3/8y) + 5y = -23

-97.75 - (34)(.375)y + 5y = -23

-97.75 - 12.75y + 5y = -23

-97.75 -7.75y = -23

-7.75y = 97.75-23=74.75

**y **= -74.75/7.75 =** -9.645161**

Substitution back into the equation for x:

x = -23/8 - 3/8(-9.645161)

x = -2.875 + 3.616935

**x** **=.741935**

8x+3y = -23 and 34x+ 5y = -23

Solving the first one for x:

8x = -23-3y

x = -23/8 - 3/8y

Substituting this value for x into the second equation:

34(-23/8 - 3/8y) + 5y = -23

-97.75 - (34)(.375)y + 5y = -23

-97.75 - 12.75y + 5y = -23

-97.75 -7.75y = -23

-7.75y = 97.75-23=74.75

Substitution back into the equation for x:

x = -23/8 - 3/8(-9.645161)

x = -2.875 + 3.616935

Dec 12, 2014 | Bagatrix Algebra Solved! 2005 (105101) for...

To find the x-intercept, set y equal to zero and solve for x.

To find the y-intercept, set x equal to zero and solve for y.

In this case the x-intercept is -3 1/8 and the y-intercept is -5.

To find the y-intercept, set x equal to zero and solve for y.

In this case the x-intercept is -3 1/8 and the y-intercept is -5.

Nov 06, 2014 | Computers & Internet

First of all you equation is not one : it has nothing on the right side of the = sign. But to answer the general question let us write the equation as **50+25x-5y=0**

**X-intercept (also know as roots) There may be several**

Definition: X-intercepts are those values of the independent variable x**for which y=0**. For a straight line there con be at most 1 x-intercept.

To find the intercept, set y=0 in the equation of the line and solve for x

50+25x-5(0)=0 or 50+25x=0. The solution is** x=-(50/25)=-2**

**Y-intercept (also know as the initial value.** There can only be 1 y-intercept, otherwise the expression does not represent a function.

Definition: It is the value of the dependent variable y when x=0 (where the function crosses the y-axis

To find it, set the x-value to 0 in the equation of the line.

**50+25x-5y=0**

50+25(0)-5y=0, or 50-5y=0. The solution is**y=50/5=10**

The straight line cuts the x-axis at the point (-2, 0) and the y-axis at the point (0,10)

Definition: X-intercepts are those values of the independent variable x

To find the intercept, set y=0 in the equation of the line and solve for x

50+25x-5(0)=0 or 50+25x=0. The solution is

Definition: It is the value of the dependent variable y when x=0 (where the function crosses the y-axis

To find it, set the x-value to 0 in the equation of the line.

50+25(0)-5y=0, or 50-5y=0. The solution is

The straight line cuts the x-axis at the point (-2, 0) and the y-axis at the point (0,10)

Jan 28, 2014 | Computers & Internet

Write the equality in the form y=(5X+3)/(4X-5). Insert parentheses to ensure a correct result.

- Multiply both sides of the equality by (4X-5). This gives (4X-5)y=(5X+3).
- Open the parentheses as 4Xy-5y=5X+3
- Subtract 5X from both sides 4Xy-5y-5X=5X-5X+3
- Add 5y to both sides 4Xy-5X-5y+5y=5y+3 or 4Xy-5X=5y+3
- Factor the X on the left side X(4y-5)=5y+3
- If 4y-5 does not vanish, you can isolate X by dividing both members of the equality by (4y-5).
- You get X=(5y+3)/(4y-5)=f(y)

Jun 24, 2012 | Mathsoft StudyWorks! Mathematics Deluxe...

Calcualte the slope of the line as

a=(7-(-11))/(10-(-5))=18/15=6/5

Use the fact that the line passes through one of the two points, for example (10,7)

7=(6/5)*10+b=12+b

Obtain b as b=7-12=-5

The equation of the line in functional form is y=(6/5)x-5

Multiply everything by 5 to clear the fraction

5y=6x-25 or 0=6x-5y-25

Finally, the equation in general form (standard?) is**6x-5y-25=0**.

Check the calculation by verifying that the point (10,7) lies on the line.

6(10)-5(7)-25=60-35-25=60-60=0 CHECKed!

Check that the second point (-5,-11) lies on the line also (if you want to)

6*(-5)-5*(-11)-25=-30+55-25=0

That checks OK.

a=(7-(-11))/(10-(-5))=18/15=6/5

Use the fact that the line passes through one of the two points, for example (10,7)

7=(6/5)*10+b=12+b

Obtain b as b=7-12=-5

The equation of the line in functional form is y=(6/5)x-5

Multiply everything by 5 to clear the fraction

5y=6x-25 or 0=6x-5y-25

Finally, the equation in general form (standard?) is

Check the calculation by verifying that the point (10,7) lies on the line.

6(10)-5(7)-25=60-35-25=60-60=0 CHECKed!

Check that the second point (-5,-11) lies on the line also (if you want to)

6*(-5)-5*(-11)-25=-30+55-25=0

That checks OK.

Dec 04, 2011 | Super Tutor Pre Algebra (ESDPALG)

X=25-y

4(25-y) + 5y=56

100-4y+5y=56

100+y=56

y= -44

x=25+44=69

x=69 y= -44

4(25-y) + 5y=56

100-4y+5y=56

100+y=56

y= -44

x=25+44=69

x=69 y= -44

Aug 22, 2008 | Curtis-Mathis CM25011 25" TV

Aug 16, 2014 | HP DeskJet F380 All-In-One Printer

19 people viewed this question

Usually answered in minutes!

×